Study of Anatomical Variation of Intrahepatic Biliary Tree by Magnetic Resonance Cholangiopancreatography in Patients Attending Tertiary Hospital of Eastern Nepal (Journal of Nobel Medical College, 2024)
Background: There are several variations in the complex anatomy of intrahepatic bile ducts. Magnetic resonance cholangiopancreatographyis a safer imaging modality that effectively shows these variations, aiding in surgical planning and preventing iatrogenic injuries. This study aims to evaluate these anatomical variations using magnetic resonance cholangiopancreatography.Materials and Methods: This cross-sectional prospective study was performed in the Radiology Department of Nobel Medical College for one year using a convenient sampling technique. A total of 165 cases meeting the inclusion criteriawere selected and magnetic resonance cholangiopancreatography was performed to evaluate the anatomical variations.Results: The mean age of patients was 34.32±10.22 years out of which 51.5%were male and 48.5%were female. The branching pattern of right hepatic duct was typical in 66.7% of cases. The right posterior sectoral duct joining left hepatic duct was the most common variation seen in 15.2%. Right posterior sectoral duct joining the common bile duct was present in 6.7%. 6.1% of cases had unclassified variation whereas a trifurcation pattern was found in 5.5%. Left hepatic duct showed the typical branching pattern in 70.9% of cases. Segment II duct draining into the common trunk of segments III and IV was seen in 20%. Triconfluence among segments II, III, and IV was seen in 8.5% and 0.6% of cases had unclassified variation.Conclusion: This study revealed wide variation in branching patterns of intrahepatic biliary ducts. The typical branching pattern of right and left hepatic ducts were seen in majority of cases.